X-ray diffraction and gamma-ray analysis of rock samples from Haradh Region in Saudi Arabia. Issue 1 (January 2019) - Al-Ghamdi, A.H.
ABSTRACT: Rock samples collected from Haradh region, Saudi Arabia were analyzed by using X-ray diffraction (XRD) spectroscopy to determine mineral composition. The XRD spectroscopy results indicate that the major, minor, and trace constituents varied from one sample to another. Also, high purity germanium (HPGe) detector was used to determine the activity concentration of U-238, Th-232 series, and K-40. The average concentration levels were 16.71, 4.41, and 55.51 Bq/kg for 226 Ra, 232 Th and 40 K, respectively. For assessing the potential radiological risks to human health, absorbed dose rate, radium equivalent activity, annual effective dose, and internal and external hazards were determined and compared with limits recommended by UNSCEAR. Results were within recommended safe ranges, meaning that the area under study is radiologically safe for habitation and can be used as construction materials.